Potential utilization of edible insects as nitrogen sources on growth characteristics and bioactive compound production in Isaria tenuipes - Pitiwittayakul, Nittaya; Wongsorn, Duanpen; Rattanasuk, Surachai (Agriculture and Natural Resources, 2023)
Importance of the work: Isaria tenuipes is an entomopathogenic fungus that has been used as a traditional medicine due to its biochemical and pharmaceutical properties. Preliminary research revealed that medium supplemented with insects promoted mycelial growth and cordycepin production. Objectives: To evaluate the suitability of edible insects as a substrate for I. tenuipes cultivation and to investigate the mycelial growth, formation of fruiting bodies and concentrations of cordycepin and adenosine. Materials & Methods: Seven edible insects were used as nitrogen sources in I. tenuipes cultivation. The mycelial growth on potato dextrose agar with different edible insects was measured on days 7, 14 and 21. Fruiting body formation and bioactive compounds were analyzed 60 d after being cultured on brown rice medium containing each edible insect. Results: Eri silkworm (Samia ricini D.) and silkworm were used to produce the fastest mycelial development on days 7 and 14, with the most extended colonies recorded at 90 mm on day 21; however, this was not significantly different from mealworm, sago palm weevil and the control. The fresh and dry weights of fruiting bodies increased in the brown rice media containing Eri silkworm. The highest cordycepin content (244 mg/100 g) and the highest adenosine content (57.7 mg/100g) were found in the fruiting bodies cultured on brown rice supplemented with Eri silkworm. Main finding: Eri silkworm could be suitable for use as a nitrogen source in I. tenuipes cultivation, resulting in a high amount of bioactive compound content.